(untitled) (GEON Journal (Management, Organizations and Business), 2019)
The global business demands, implicitly raise terms such as business competitiveness, decision making and ability to manage innovative business projects. This opens a range of possibilities to work in areas of competence from the training of administrators. The Tunning Project in Latin America (TAL) (2007) is a determining reference for the development of this research. Although, one of the objectives of the TAL project has been to promote at the Latin American scale, lines of convergence in twelve thematic areas, such as; Business Administration, Education, Architecture, among others. It is in the first thematic area that the present investigation was addressed. Being a plot in the Bachelor of Business Administration of the School of Management of the BUAP. Meanwhile, the methodological framework is qualitative, although it is not ruled out that, for the analysis of the results obtained, this research has been based on numerical and graphic data. Additionally, the structured interview technique was applied, considering as a basis the basic instrument a questionnaire, per se, of the project